Extracorporeal therapies in sepsis: a comprehensive review of the Selective Cytopheretic Device, Polymyxin B and Seraph cartridges - Lucas Yessayan; Chris J. Pino; H. David Humes (Renal Failure)
Sepsis, a dysregulated host response to infection, is a leading cause of morbidity and mortality in critically ill patients, despite advancements in antimicrobial therapies. Recent innovations in extracorporeal blood purification therapies, such as the Selective Cytopheretic Device (SCD), Polymyxin B Hemoperfusion Cartridge (PMX-HP), and Seraph 100 Microbind Affinity Blood Filter (Seraph), have demonstrated promising potential as adjuncts to conventional therapies. The SCD targets activated white blood cells, while PMX-HP binds endotoxins in Gram-negative sepsis. The Seraph targets a broad range of pathogens, including viruses, bacteria and fungi. Evidence from several clinical trials and observational studies indicate that these therapies can improve organ function, and potentially improve survival in patients with sepsis. Despite the strong pathophysiological rationale for using these devices in sepsis, conclusive evidence of their effectiveness remains limited. Multicenter randomized controlled trials are currently underway with each of these devices to establish their role in improving patient outcomes. Further research is needed to establish optimal protocols for their initiation, duration, and integration into standard sepsis management.